Application of a discrete simulation model to improve the productivity of the production process in a manufacturing company - Vásquez Álvarez, Orlando (2023)
In this article, a simulation model was developed to propose and evaluate improvements that increase the productivity of the production process of a manufacturing company and at the same time help achieve the company's objectives, for which the Promodel simulation software was used. The study begins with the conceptualization of the model explaining the operation of the production process of the company, detailing the transactions used in the operations and then presenting the layout of the model with the different locations, entities and resources provided by the production process. And finally the results of the model are transcribed with the new values of the variables that intervene in the process and with these values compare it with the current ones and obtain the conclusions of productivity improvement.